Prospective teachers’ thinking through realistic mathematics education based emergent modeling in fractions - Ekasatya Aldila Afriansyah; Turmudi Turmudi (Universitas Hamzanwadi, 2022)
The unconsciousness of a teacher in obtaining knowledge due to students can be known if the teacher was notified when he was a student. A student has an essential role in learning, and the teacher is responsible for supporting smooth learning. Students' problem-solving processes need to be found because each student's reasoning and ideas in solving problems are different. This study focuses on students' thinking processes using realistic mathematics education based on emergent modeling. In this study, the researcher is the teacher, and the student is the prospective teacher. The prospective teacher involved were students of the Institut Pendidikan Indonesia mathematics study program. Prospective teachers were selected as research subjects for as many as 74 people (11 males and 63 females) consisting of 3 classes. The research method uses descriptive qualitative. As learning activities progress, students get a kind of model that seems as solutions to solving problems given by the teacher. Various kinds of models emerged from various student ideas and ended with a mutually agreed for a model for. Through this study, a teacher can learn about student models in the learning process.